2003
DOI: 10.1023/a:1023277413027
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In a sample of 585 children assessed in kindergarten through 8th grade, we fit a confirmatory factor model to both mother- and teacher-reported symptoms on the Achenbach checklists (CBCL, TRF) and determined that a covariation factor of externalizing and internalizing behaviors existed, in addition to the pure-form factors of externalizing and internalizing for each reporter. In 3 structural equation models, between 8 and 67% of the variance in these 6 latent factors was accounted for by a set of antecedent ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
93
5
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(116 citation statements)
references
References 50 publications
14
93
5
4
Order By: Relevance
“…Although depression has been shown to increase from early adolescence until adulthood for girls (e.g., Galambos et al 2003), in the current study, depression slightly increased from age 12 to around age 17, followed by a decrease from age 17 to 20. This is consistent with findings showing that internalizing problem shows a curvilinear shape across adolescence (Keiley et al 2003;Lansford et al 2006). For boys, depression decreased from early to late adolescence, which is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…Although depression has been shown to increase from early adolescence until adulthood for girls (e.g., Galambos et al 2003), in the current study, depression slightly increased from age 12 to around age 17, followed by a decrease from age 17 to 20. This is consistent with findings showing that internalizing problem shows a curvilinear shape across adolescence (Keiley et al 2003;Lansford et al 2006). For boys, depression decreased from early to late adolescence, which is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings indicated that girls were more likely to have a provisional diagnosis of mood, sleep, or anxiety disorder; whereas, boys were more likely to carry a provisional diagnosis of ADHD. This finding is a replication of previous research suggesting that young boys are far more likely to receive diagnoses along the externalizing spectrum; whereas, girls are more likely to receive diagnoses of internalizing disorders (e.g., Achenbach, Howell, Quay, Conners, & Bates, 1991;Dodge, Pettit, & Bates, 1994;Keiley et al, 2003). Importantly, there are many shared behaviors between various mental health disorders and potential reactions to traumatic events.…”
Section: Discussionsupporting
confidence: 81%
“…Psychology Sex differences are also important to consider when looking at diagnoses in childhood. The extant research evidence suggests that girls are more likely to show symptoms of internalizing disorders (e.g., anxiety, depression) and boys more likely to exhibit behaviours indicative of externalizing disorders (e.g., ADHD, conduct disorder) (Achenbach, Howell, Quay, Conners, & Bates, 1991;Dodge, Pettit, & Bates, 1994;Keiley et al, 2003). As such, the current study also considered sex differences while exploring the relation between traumatic stress and childhood mental health disorders.…”
Section: Current Studymentioning
confidence: 98%
“…23,24 Girls show higher mean levels of internalizing symptoms than boys, as well as sharper increases in internalizing symptoms from childhood to adolescence. 25,26 Maternal employment may have a negative effect on an adolescent's mental health if employment leads to deficient parenting practices. 27 In the poor urban community where our study was conducted, women are usually overloaded with activities and obligations at home and outside and are frequently the main financial provider in the family.…”
Section: Special Theme -Childhood Injuries and Violencementioning
confidence: 99%